Technical Efficiency of Indonesian Potato Farming during Rainy and Dry Seasons: Evidence from Merangin District, Indonesia - Yusnina, Yusnina; Syaukat, Yusman; Hartoyo, Sri; Fariyanti, Anna (Agro Bali : Agricultural Journal, 2024)
Potatoes are among the vegetables highly susceptible to climate change, and its consequences can significantly affect technical efficiency.However, the production of potato relatively fluctuated due to some factors influencing it. The study aims to analyze the factors affecting potato production, measure the level of technical efficiency in potato farming, and identify the socio-economic factors that influence technical inefficiency in potato farming, both in the rainy and dry seasons. The study was conducted in Merangin Regency, Jambi Province. A purposive sampling method was used to select the research area and collect data from 102 potato farmers. The data were analyzed using the Stochastic Frontier Cobb-Douglas production function model with a maximum likelihood estimation (MLE) approach. The research results show that land and seed variables significantly influence potato production, both in the rainy and dry seasons. Meanwhile, fertilizer P and labor only significantly influence the dry season. The average level of technical efficiency in the dry season (0.89) is higher than in the rainy season (0.73). The results of the average difference test (t-test) show that in the dry season, the level of technical efficiency has a higher value than in the rainy season, with a significance of 1%. The significant socio-economic variables influencing technical efficiency are membership in farmer groups.